Effects of Different Tillage Practices on Slope Erosion Characteristics of Peanut Field - Liang, Xinlan; Song, Ke; Zhang, Youheng; Huang, Hongliang; Wang, Yong; Cao, Ying (Agronomy (Basel), 2023)
Under three rainfall intensities (60–90–120 mm/h) and four tillage practices (longitudinal ridge tillage, cross ridge tillage, flat tillage and hole sowing), field experiments was conducted during the podding stage of peanuts to investigate the changes in hydrodynamic parameters and the erosion response on purple soil slope cropland in order to reveal the soil and water conservation benefits of different tillage practices. The results showed that: (1) The sediment yield of the four tillage practices was ranked in descending order: longitudinal ridge tillage, flat tillage, hole sowing, and cross ridge tillage. Under the same rainfall intensity, there were no significant differences in runoff among these four tillage practices (p > 0.05), whereas sediment yield varied significantly. (2) The average flow velocity, Reynolds number, and Froude number of each treatment were positively correlated with rainfall intensity, while the resistance coefficient was negatively correlated. Flat tillage and cross ridge tillage were intermediate. The Reynolds number and Froude number of each treatment did not exceed the critical value and were generally within the laminar flow range, except for the longitudinal ridge tillage treatment at 120 mm/h rainfall intensity. (3) The sediment yield intensity on the slope was negatively correlated with the resistance coefficient, following a power function. The runoff shear stress and runoff power on each treatment were both positively correlated with sediment yield intensity in a linear manner. Compared to longitudinal ridge tillage, the other three tillage practices showed much better soil and water conservation benefits. Among them, cross ridge tillage exhibited the best water storage and soil conservation effects. In terms of hydraulics, longitudinal ridge tillage and flat tillage increased the erosive force required for sediment initiation and suppressed erosion occurrence. The research results were of great significance in revealing the characteristics of runoff erosion in purple soil areas and controlling tillage practices for soil erosion in purple soil areas.